8. INSOMNIA AND RELATED FACTORS AMONG THE ELDERLY LIVED IN TAN VINH COMMUNE, LUONG SON DISTRICT, HOA BINH PROVINCE, 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to assess the prevalence of insomnia and its associated factors among the elderly in Tan Vinh, Luong Son District, Hoa Binh Province, in 2024.Subject Methods: A cross-sectional design was conducted in 255 elderly lives in Tan Vinh, Luong Son District, Hoa Binh Province from March to August 2024. Insomnia Severity Index was used to collect the data.Results: 77.3% of participants reported insomnia; among them, 11.6% were classified as severe insomnia. Individuals who were unmarried, divorced, or widowed were found to be 2.9 times more likely to experience insomnia compared to married participants. Additionally, those who consumed stimulants late in the evening faced a staggering 12.1-fold increased risk of insomnia. Furthermore, elderly individuals who napped for more than 30 minutes had a 3.9 times higher likelihood of insomnia compared to those who napped for less than 30 minutes.Conclusion: The study indicated a high prevalence of insomnia among participants that highlight the needs for interventions to improve sleep quality among participants.
Keywords: Insomnia; elderly; Hoa Binh; ISI